Digital Storytelling Strategy for Teaching Arabic Language: The Success Formula of Developing Active Listening and Creative Thinking Skill - M. Al-Hileh, Mohamed; A.S. Tabieh, Ahmad; M.J. Abu Afifa, Haya (International Journal of Psychosocial Rehabilitation, 2020)
This study aims at investigating the effect of teaching the Arabic language by using digital storytelling for basic third-grade pupils in developing active listening skills and creative thinking. A purposive sample that consisted of (36) male and female pupils from the basic third grade were selected. They were divided into two groups which were the experimental and control. Two tests were used: post active listening and creative thinking tests. The validity and reliability of the tests were assured. The findings showed that there were no significant differences in (α ≤ 0.05) between the means of the post active listening test in Arabic, in favor of the experimental group, but there were no significant differences in (α ≤ 0.05) between the means of the post creative thinking test in Arabic attributed to any of the two groups.